Two-step Registration in 3D Human Body Scanning Based on Multiple RGB-D Sensors (Journal of Fiber Bioengineering and Informatics, 2015)
In this paper, we propose a universal registration method for the body scanner consists of multiple\rfixed sensors. Firstly, a new double-faced checkerboard is designed to apply calibration method into the\rinitial estimations of the relative poses of point clouds. Secondly, ICP (Iterative Closet Point) algorithm\ris utilized for further registration. Since ICP algorithm may fail in situations of outliers, ambiguity or\rmissing data, we make full use of the geometry feature of creased papers to solve these problems. A new\rbody scanning system with fast capture speed is also proposed to validate our method. The experiment\rresults demonstrate our approach is robust and fast.